Automated smart car parking system using raspberry Pi 4 and iOS application - Rahman Atiqur; Yun Li (International Journal of Reconfigurable and Embedded Systems (IJRES), 2020)
In interconnection and automation of different physical gadgets, vehicles, home machines and different things, the internet of things (IoT) innovation plays a critical role. These objects associate and deal information with the assistance of software, different sensors, and actuators. A human's standard of life and living are improved with this automation of gadgets, which is a forthcoming need. In this paper we talked about a similar requirement for instance, a smart car parking system which empowers a driver to discover a parking area and a free slot in that parking area inside a city. This paper focus on decreasing the time squandered on discovering parking area. This in turn diminishes the fuel utilization and way of life. With the exponential increment in the quantity of vehicles and total population, vehicle accessibility, use out, about starting late, finding a space for parking the vehicle is turning out to be increasingly more troublesome with realizing the amount of conflicts, for example, automobile overloads. This paper is connected to making a trustworthy system that accept authority over the undertaking of recognizing free slots in a parking area and keeping the record of vehicles left in an extremely methodical way. The predicted system decreases human effort at the parking area generally, for example, in case of looking of free slots by the driver and calculating the portion for each vehicle using parking area. The different advances engaged with this system are vehicle unique proof utilizing RFID labels; free slot discovering utilizing Ultrasonic sensors and payment count is done based on time of parking.